2017
DOI: 10.1080/00015385.2017.1291133
|View full text |Cite
|
Sign up to set email alerts
|

The impact of non-dipper circadian rhythm of blood pressure on left ventricular hypertrophy in patients with non-dialysis chronic kidney disease

Abstract: Objective The aim of this study was to investigate the correlation between non-dipper circadian rhythm of blood pressure (BP) and left ventricular hypertrophy (LVH) in patients with chronic kidney disease (CKD). Methods and results All 257 patients with stage 1 to 5 CKD were enrolled in the study and classified into a CKD1-3 group and a CKD4-5 group according to renal function. The parameters and circadian rhythm of BP were measured by a GE Marquette Tonoport V Eng dynamic sphygmomanometer, and cardiac structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Taking into consideration that non-dipping BP pattern is associated with suppression of parasympathetic nervous system activity and an increase in sympathetic nervous system activity throughout the night, it appears that hypersympathicotonia significantly influence not only 24-hour BP profile and AH development, but also CKD progression [20]. In the view of most clinicians, the non-dipping circadian rhythm of BP in CKD patients is closely linked to cardiovascular complications, particularly, left ventricular hypertrophy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration that non-dipping BP pattern is associated with suppression of parasympathetic nervous system activity and an increase in sympathetic nervous system activity throughout the night, it appears that hypersympathicotonia significantly influence not only 24-hour BP profile and AH development, but also CKD progression [20]. In the view of most clinicians, the non-dipping circadian rhythm of BP in CKD patients is closely linked to cardiovascular complications, particularly, left ventricular hypertrophy [21].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in the Syst-Eur study, higher incidence of stroke and myocardial infraction was revealed in non-dipper patients [35]. In patients with circadian BP profile disorders such complications like LVH, microalbuminuria, thickening of the intima media in the carotid artery and neurological incidents are significantly more common [36,37,38]. Finding of increased incidence of concentric hypertrophy (CH) may partially explain the higher incidence of cardiovascular events in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic nervous activity in the human body is the weakest at night when the muscles are relaxed sufficiently, and peripheral vascular resistance is also minimized, and during this period blood pressure is a good indicator of the degree of disease [16]. The results of the present research showed that the circadian rhythm disorder group had remarkably higher d-SBP, d-DBP, and d-PP but lower n-SBP, n-DBP, and n-PP than in the normal circadian rhythm group, which may be related to the strengthened stress-sensitivity of sympathetic nervous system activity and decreased function of vagus nerve in patients with circadian rhythm disorder of blood pressure, suggesting that such patients have severe hypertension.…”
Section: Discussionmentioning
confidence: 99%